The Well-being and Instructional Experiences of K-12 Music Educators: Starting a New School Year During a Pandemic - Parkes, Kelly A.; Russell, Joshua A.; Bauer, William I.; Miksza, Peter (Frontiers in Psychology, 2021)
In adapting to remote emergency teaching modes during pandemic-imposed conditions, teachers’ instruction has changed dramatically. Early research indicates that the well-being of music teachers has suffered during the COVID-19 pandemic and that high levels of depression are widespread. The purpose of this survey study was to assess the continued psychological well-being of music teachers working amid a global pandemic based upon previous research we conducted during the Spring 2020 semester when most teachers in the United States were forced into emergency remote teaching. A secondary purpose was to explore the ways that pandemic conditions have affected music teachers’ sense of safety at work and their current teaching situations. Our questionnaire consisted of sections pertaining to (1) demographic and institutional information, (2) well-being and depression, (3) instructional format and preparedness, (4) teaching efficacy compared to the start of the pandemic, and (5) potential positive outcomes of the pandemic-imposed adjustments. In total, 1,325 music teachers responded to our survey. Overall, the participants reported poorer well-being than both published norms and the sample of participants in our previous study. In addition, 17% reported mild depression, 25% reported moderate depression, and 24% reported severe extremely severe levels of depression. Summaries of the participants instructional experiences and their implications for music education are discussed within.